Dormancy in parental lines of sunflower (Helianthus annuus) seeds and its alleviation - SINGH, GURMIT; BAJAJ, R K; SANDHA, G S; SHARMA, H L (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted on sunflower (Helianthus annuus L.) seed of autumn crop (harvested in January 1991) to study dormancy in parental lines and its alleviation. Nine genotypes including A (male-sterile), R (restorer) and B (maintainer) lines of new hybrids were screened for determining seed-dormancy period. Genotypic response for dormancy period was observed with 'RHA 274' (15-30 days); 'RHA 83R6' , 'RHA 297' and '234 B' (31-45 days); '207 B' (46-60 days); 'RHA 6D1' and 'RHA 856' (61-75 days) and 'RHA 272' and '86 B3' (76-90 days). Soaking of the dormant seeds in water and soiutions of potassium nitrate (KNO3 200 ppm), thiourea (100,200 and 500 ppm), ethrel (100, 250 and 500 ppm) and GA3 (100, 250 and 500 ppm) for 24 hr improved the seed germination by 69.6-86.6; 66-81.6; 65-80; 70.0-86.6 and 78-95% respectively. Soaking of seeds in GA3 at all concentrations provided the highest germination (%)However, the minimum germination standard (70%) could be achieved by soaking in water for 24 hr.